2003
DOI: 10.1002/chin.200323219
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Some High Al Content Glasses in Various Lanthanide‐Si—Al—O—N Systems

Abstract: Inorganic chemistryInorganic chemistry Z 0100 Properties of Some High Al Content Glasses in Various Lanthanide--Si-Al-O-N Systems-[25 refs.]. -(REDINGTON, W.; REDINGTON, M.; HAMPSHIRE, S.; SERANTONI, M.; J. Non-Cryst. Solids 316 (2003) 1, 74-81; Dep. Mater. Sci. Technol., Univ. Limerick, Limerick, Ire.; Eng.) -Schramke 23-219

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Poisson's ratio relates to the rigidity of the glass network and its dimensionality, where a higher (lower) ν value normally correlates with a lower (higher) network connectivity/rigidity 56,72 . Yet, oxynitride glasses generally exhibit higher Poisson's ratios than their N‐free aluminosilicate‐based counterparts 30,44,99,103 . The present Ca–Al–Si–O–N glasses reveal a narrow span of Poisson's ratios between 0.260 and to 0.278 for the I‐3.2 and II‐7.2 glass specimens, respectively (Table 2).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Poisson's ratio relates to the rigidity of the glass network and its dimensionality, where a higher (lower) ν value normally correlates with a lower (higher) network connectivity/rigidity 56,72 . Yet, oxynitride glasses generally exhibit higher Poisson's ratios than their N‐free aluminosilicate‐based counterparts 30,44,99,103 . The present Ca–Al–Si–O–N glasses reveal a narrow span of Poisson's ratios between 0.260 and to 0.278 for the I‐3.2 and II‐7.2 glass specimens, respectively (Table 2).…”
Section: Resultsmentioning
confidence: 81%
“…56,72 Yet, oxynitride glasses generally exhibit higher Poisson's ratios than their N-free aluminosilicate-based counterparts. 30,44,99,103 The present Ca-Al-Si-O-N glasses reveal a narrow span of Poisson's ratios between 0.260 and to 0.278 for the I-3.2 and II-7.2 glass specimens, respectively (Table 2). The minute variations of the Poisson's ratio did not suggest any clearly identifiable trend against n N or any other glass constituent.…”
Section: Elastic Propertiesmentioning
confidence: 81%
See 1 more Smart Citation
“…The values have been found to vary linearly with N content, density of the glass and ionic radius of rare-earth (RE) glass modifier/dopant, with the effects of N and RE contents being independent and additive. 6,7 Studies of compositional dependencies of hardness are predominant for glasses containing, in addition to Si, Y and Al, 1,2,[8][9][10][11][12] and RE and Al, 5,[13][14][15] with the latter mainly concerning variations with the ionic radius and/or cationic strength * Corresponding author. Tel.…”
Section: Introductionmentioning
confidence: 99%
“…Glass forming regions and properties of oxy-nitride glasses [1][2][3][4][5] have been studied chiefly because they occur as grain-boundary phases in silicon nitride ceramics, in which the composition and volume fraction of them determine the properties of the materials, particularly the high-temperature mechanical properties. The studies have shown that a number of physical and mechanical property values, including hardness, fracture toughness, elastic modulus and refractive index, increase with increasing nitrogen content.…”
Section: Introductionmentioning
confidence: 99%